Pelaksanaan Program Baca Tulis Al-Qur'an (BTQ) terhadap Peserta Didik Kelas VII - 'Aini, Hanifa Rahmatul; Muliati, Indah (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the effectiveness of the Qur’anic Literacy Program (Baca Tulis Al-Qur’an or BTQ) in private madrasahs, despite the continued prevalence of Qur’anic illiteracy among students, particularly at the Madrasah Tsanawiyah level. The aim of this research is to describe the implementation of the BTQ program in eradicating Qur’anic illiteracy among seventh-grade students at MTsS TI Batang Kabung in Padang City. A qualitative approach with a case study design was used, and participants were selected through purposive sampling, including the principal, BTQ instructors, and students from the BTQ group. Data collection techniques included observation, semi-structured interviews, and documentation, which were analyzed using the Miles and Huberman interactive model: data reduction, data display, and conclusion drawing. The findings show that the BTQ program is categorized into three groups based on student ability: beginner (Iqro’ volumes 1–3), intermediate (Iqro’ volumes 4–6), and advanced (using the talaqqi method). Activities are conducted routinely every Monday from 14.00 to 15.00 WIB. The program has proven effective in improving students’ abilities in reading, writing, and memorizing the Qur’an, while also fostering religious enthusiasm. The conclusion of this study is that a stepwise approach in the BTQ program can significantly enhance Qur’anic literacy. The implication of this research is the need for developing a skill-based BTQ learning model that can be replicated in other Islamic educational institutions as a systematic strategy to eradicate Qur’anic illiteracy.